2019
DOI: 10.1192/bjb.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

The London memory service audit and quality improvement programme

Abstract: Aims and methodMemory services have expanded significantly in the UK, but limited performance data have been published. The aim of this programme was to determine variation in London memory services and address this through service improvement projects. In 2016 London memory services were invited to participate in an audit consisting of case note reviews of at least 50 consecutively seen patients.ResultsTen services participated in the audit, totalling 590 patients. Variation was noted in neuroimaging practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…This heterogeneity of aetiologies between and within individuals with cognitive impairment creates wide variation in diagnosis, prognosis and therapeutic approach. Without tissue-based diagnosis, clinico-pathological correlation is exceptionally poor, both in leading centres and routine practice [ 21 ], also in UK routine practice [9].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…This heterogeneity of aetiologies between and within individuals with cognitive impairment creates wide variation in diagnosis, prognosis and therapeutic approach. Without tissue-based diagnosis, clinico-pathological correlation is exceptionally poor, both in leading centres and routine practice [ 21 ], also in UK routine practice [9].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“… 11 However, this supports previous data from the London memory audit services, where only 15% of those referred under 65 received a dementia diagnosis. 12 Instead, the majority in this group were diagnosed with mild cognitive impairment or other psychiatric disorders. Our analysis of HoNOS scores of patients on entry to the service did not broadly support the idea that YoD patients, at least at presentation, suffer from more neuropsychiatric disturbance.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence from UK services suggests considerable variation in the use of imaging in the investigation of cognitive impairment. The 2019 London memory service audit 77 reported that the percentage of patients deemed not to require a scan for dementia diagnosis varied from 6% to 46%. Of those patients who did have a scan, the percentage who received computerised tomography (CT) (rather than MRI) varied from 2% to 58%.…”
Section: Imagingmentioning
confidence: 99%